ChemInform Abstract: Synthesis of Pyrazolo[4′, 3′:3, 4]pyrido[1, 2‐a]benzimidazoles and Related New Ring Systems by Tandem Cyclization of vic‐Alkynylpyrazole‐4‐carbaldehydes with (Het)aryl‐1, 2‐diamines and Investigation of Their Optical Properties. Issue 37 (September 2015) - Milisiunaite, Vaida; Arbaciauskiene, Egle; Bieliauskas, Aurimas; Vilkauskaite, Gyte; Sackus, Algirdas; Holzer, Wolfgang
Abstract The reaction of vic‐alkynylpyrazole‐4‐carbaldehydes (I) and (XII) with o‐phenylenediamine (II) leads to the tetracyclic products (III) and (XIII), respectively.